Emotional regulation strategies in daily life: the intensity of emotions and regulation choice - Kozubal, Magdalena; Szuster, Anna; Wielgopolan, Adrianna (Frontiers in Psychology, 2023)
Emotion regulation is an adaptive ability affecting people's physical and mental health, quality of life and functioning. In the present study we focused on the influence of the intensity of experienced emotions on emotion regulation strategies (ERS) that are applied in everyday life. For 7 days the participants kept an online diary where every day they described the situation which had aroused their strongest negative emotions. Next, they identified the emotions, their intensity and the type of applied strategies (acceptance vs reappraisal vs rumination vs distraction vs suppression). The study involved 88 people N=88, which gives 538 observations. The obtained results indicate that the intensity of emotions affects the choice of regulation strategies. When the intensity increases, people are more likely to choose the rumination strategy and less likely to choose the reappraisal strategy. However, the expected relationship between the intensity and the number of regulation strategies was not confirmed. In turn, it was gender (male) that turned out to be associated with a greater number of strategies used.